The Effect of Branding on Customer Loyalty - A Case Study on the Leading Brand (Mobilink) and its comparison with the Follower Brands - Khalid, Sana (2009)
Branding is becoming an important aspect for service organizations as it enables them to make an identity and attract customers. To date, research has mainly focused on developed countries and developments in the developing countries have been overlooked. Due to lack of academic contribution regarding the effect of branding on customer loyalty in the telecommunication sector of Pakistan, this research intends to fill the gap in the marketing literature by adding knowledge in this area. The research intends to analyze the effect of branding on consumer loyalty by making a comparative analysis between a market leader (Mobilink) and the follower brands. The study intends to identify elements which help in building a strong brand, and can lead to a loyal customer base. In order to do so, the research investigates the link between brand awareness, brand associations, brand image, quality,satisfaction and customer loyalty and also explores the brand portfolio of the market leader and its effect on brand image that leads to customer loyalty. A combination of qualitative and quantitative methods was employed which showed that it is important to brand a service due to its positive impact on loyalty. Customer loyalty contributes significantly towards the success of any organization as it allows charging higher prices,acceptance of brand extensions and consumers spread positive word of mouth. It was also found that by branding a service helps a firm to maintain firm foothold as it becomes difficult for customers to switch even if a superior brand enters the market. Likewise brand portfolio management is critical to ensure customer satisfaction which ultimately leads to a loyal customer base. If these strategies are managed well, a brand can become market leader. Finally, a discussion on managerial implications is given along with recommendations for future research. Key words: Customer Loyalty, Brand Awareness, Brand Associations, Brand Image, Quality and Satisfaction.